The Role of Neuroinflammation in Glaucoma: An Update on Molecular Mechanisms and New Therapeutic Options - Rolle, Teresa; Ponzetto, Antonio; Malinverni, Lorenza (Frontiers in Neurology, 2021)
Glaucoma is a multifactorial optic neuropathy characterised by the continuous loss of retinal ganglion cells, leading to progressive and irreversible visual impairment. In this minireview we report the results of the most recent experimental studies concerning cells, molecular mechanisms, genes and microbiome involved in neuroinflammation processes correlated to glaucoma neurodegeneration. The identification of cellular mechanisms and molecular pathways related to retinal ganglion cell death is the first step towards the discovery of new therapeutic strategies. Recent experimental studies identified the following possible targets: adenosineA2A receptor, sterile alpha and TIR motif containing 1 (neurofilament light chain), Toll-like receptor (TLR) 2 and 4, Phosphodiesterase type 4 (PDE4) and FasL-Fas signaling (in particular ONL1204, a small peptide antagonist of Fas receptors), and therapies directed against them. The continuous progress in knowledge provides interesting data, although the total lack of human studies remains an important limitation. Further research is required to better define the role of neuroinflammation in the neurodegeneration processes that occur in glaucomatous disease, and to discover neuroprotective treatments amenable to clinical trials. The hereinafter reviewed studies are reported and evaluated according to their translational relevance.